Autoimmune Gastritis in the Pediatric Age: An Underestimated Condition Report of Two Cases and Review - Saglietti, Chiara; Sciarra, Amedeo; Abdelrahman, Karim; Schneider, Vanessa; Karpate, Arti; Nydegger, Andreas; Sempoux, Christine (Frontiers in Pediatrics, 2018)
Background: diagnosis of pediatric autoimmune gastritis (AIG) in children is important due to poor outcome and risk of malignancy. This condition is often underestimated in the clinico-pathologic diagnostic work-up, leading to delayed time-to-diagnosis. To increase the awareness of this condition in the pediatric population, we present two cases encountered at our institution, discuss their clinical, biological and histological presentations in relation with evidence from the literature, and propose an algorithm for diagnosis and follow-up of AIG in children. Case presentation: two patients (12 and 17 years old) presented with iron deficiency anemia and negative family history for autoimmune disorders. In both cases, the final diagnosis of autoimmune gastritis was delayed until pathological examination of endoscopic gastric biopsies showed atrophy of oxyntic glands. H. pylori search was negative. Follow up biopsies revealed persistent disease. Literature review on this condition shows unclear etiology and poor long term outcome in some patients because of increased risk of malignancy. Conclusions: AIG should be considered in the differential diagnosis of iron deficiency anemia in the pediatric population. Standardized clinico-pathologic work-up is mandatory. Endoscopic follow-up should be performed due to the risk of malignancy.